Uniqueness, complexities, and research issues of logistics and trade facilitation in Greater Bay Area of China - Edmund Y. Wu; Danny Chi Kuen Ho; Stephen C. H. Ng; Lawrence C. Leung (Journal of Shipping and Trade (JST), 2023)
The Greater Bay Area (GBA) is to become a major innovation and technology hub of global impact. Such a transformation is to take place in the midst of a policy-driven economy in GBA's Mainland region and a market-driven economy in Hong Kong and Macau. In this paper, we examine the uniqueness and complexities of logistics and trade facilitation in GBA. This study establishes a discourse in GBA's logistics and trade facilitation between government and non-government stakeholders. Based on the discourse, we provide a conceptual context on the unique aspects of GBA, pinpointing critical issues such as the coexistence of differing institutional systems and interplay between state planning and market economy. A major objective of the paper is to identify and conceptualize unique logistics and trade features of GBA development, and to highlight opportunities for academic and policy research.
Keywords: 650; Academic and policy research; Greater Bay Area of China; Logistics & trade facilitation and integration; Stakeholder concerns